Education for Sustainability in Foreign Language Curricula in Algeria: The Case of the FLE Curriculum for the First Year of Middle School - Hamaizi , belkacem (El Omda in Linguistics and Discourse Analysis, 2022)
Training young learners in the concept of sustainability through foreign languages, particularly FLE, is a major challenge. It is closely linked to key educational issues aimed at enabling learners to participate and make informed decisions in an uncertain world. This contribution examines the extent to which the curriculum—specifically the French curriculum designed for first-year middle school learners in Algeria—contributes to the development of sustainability awareness among learners. The analysis revealed that the curriculum under study does address the theme of sustainability; however, a persistent deficiency has been observed regarding the strategies for teaching it.